Caveolin modulates integrin function and mechanical activation in the cardiomyocyte. Issue 2 (3rd November 2014) - Israeli‐Rosenberg, Sharon; Chen, Chao; Li, Ruixia; Deussen, Daniel N.; Niesman, Ingrid R.; Okada, Hideshi; Pately, Hemal H.; Roth, David M.; Ross, Robert S.
ABSTRACT: β1 integrins (β1) transduce mechanical signals in many cells, including cardiac myocytes (CM). Given their close localization, as well as their role in mechanotransduction and signaling, we hypothesized that caveolin (Cav) proteins might regulate integrins in the CM. β1 localization, complex formation, activation state, and signaling were analyzed using wild‐type, Cav3 knockout, and Cav3 CM‐specific transgenic heart and myocyte samples. Studies were performed under basal and mechanically loaded conditions. We found that: 1) β1 and Cav3 colocalize in CM and coimmunoprecipitate from CM protein lysates; 2) β1 is detected in a subset of caveolae; 3) loss of Cav3 caused reduction of β1D integrin isoform and active β1 integrin from the buoyant domains in the heart; 4) increased expression of myocyte Cav3 correlates with increased active β1 integrin in adult CM; 5) in vivo pressure overload of the wild‐type heart results in increased activated integrin in buoyant membrane domains along with increased association between active integrin and Cav3; and 6) Cav3‐deficient myocytes have perturbed basal and stretch mediated signaling responses. Thus, Cav3 protein can modify integrin function and mechanotransduction in the CM and intact heart.—Israeli‐Rosenberg, S., Chen, C., Li, R., Deussen, D. N., Niesman, I. R., Okada, H., Patel, H. H., Roth, D. M., Ross, R. S. Caveolin modulates integrin function and mechanical activation in the cardiomyocyte. FASEB J . 29, 374‐384 (2015). www.fasebj.org